2016
DOI: 10.1186/s12879-016-1863-x
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide distribution of varicella-zoster virus clades in China

Abstract: BackgroundIn 2010, a universal nomenclature for varicella-zoster virus (VZV) clades was established, which is very useful in the monitoring of viral evolution, recombination, spread and genetic diversity. Currently, information about VZV clades has been disclosed worldwide, however, there are limited data regarding the characterization of circulating VZV clades in China, even where varicella remains widely epidemic.MethodsFrom 2008 to 2012, clinical samples with varicella or zoster were collected in General Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…VZV strains have been classified into seven clades including two preliminary ones [6], in addition, clades VIII and IX were reported [12] (Table 3). Genotyping 15 of the 44 strains showed that samples from England were either clade 1 or 3, whilst the samples from China were clade 2 or in once case clade 4 (Table 1) confirming previous reports that clades 1 and 3 predominately circulate in Europe and the Americas, clade 2 is mainly found in Korea, Japan and China, and clades 4 and 5 are mainly detected in India, Nepal, Bangladesh and Africa [612, 27, 34]. To show that the technique could be used elsewhere for distinguishing between wt and vaccine VZV in various clades, especially clade 2 as vaccine Oka belongs to clade 2, it is important that this method was shown to work in representative clade 2 samples.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…VZV strains have been classified into seven clades including two preliminary ones [6], in addition, clades VIII and IX were reported [12] (Table 3). Genotyping 15 of the 44 strains showed that samples from England were either clade 1 or 3, whilst the samples from China were clade 2 or in once case clade 4 (Table 1) confirming previous reports that clades 1 and 3 predominately circulate in Europe and the Americas, clade 2 is mainly found in Korea, Japan and China, and clades 4 and 5 are mainly detected in India, Nepal, Bangladesh and Africa [612, 27, 34]. To show that the technique could be used elsewhere for distinguishing between wt and vaccine VZV in various clades, especially clade 2 as vaccine Oka belongs to clade 2, it is important that this method was shown to work in representative clade 2 samples.…”
Section: Discussionsupporting
confidence: 85%
“…The 16 samples collected from Chinese patients comprised 11 chickenpox samples and five shingles samples. Nine of the samples had previously been genotyped [27] and belonged to clades 2 and 4 ( Table 1). The vaccination histories of Chinese patients were unknown, but routine varicella and shingles vaccination is not offered in China.…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypic prevalence of VZV in China showed that VZV genotype J was the major prevalent strain from 2008 to 2012. In addition, VZV genotypes M1 and M2 also circulated in Guangdong [17]. VZV genotype J was also the dominant pathogen of VZV infection in Chinese children during August 2017-September 2017 in Suzhou, Jiangsu [18].…”
Section: Discussionmentioning
confidence: 99%
“…The varicella vaccine has been applied in China for more than 30 years, and the vaccine strains from VZV infected individuals are distributed epidemiologically (8).…”
Section: Introductionmentioning
confidence: 99%